Pengukuran Budaya Keselamatan Pasien di Pelayanan Kesehatan Primer: Literature Review - Davina Mutia; Inge Dhamanti (Jurnal Kesehatan Komunitas, 2023)
Background: Patient safety research has primarily focused on hospitals, despite the fact that patient safety incidents in primary care are quite common. Patient safety incident in primary care caused by the implementation of patient safety culture has not been widely applied. Measuring patient safety culture can improve primary care patient safety and decrease patient safety incidents. Objective:  To identify patient safety culture dimensions with low scores that require improvement in primary care. Methods: Article searches were conducted through the PubMed and ScienceDirect databases using the keywords “patient safety” AND “safety culture” AND “primary care”. A total of 199 articles were found, and only 10 articles fit the inclusion criteria. Results:  The SAQ-AV, MOSPSC, and HSOPSC patient safety culture measurement instruments were used in 242 primary healthcare settings across eight countries. According to research, each primary care setting has aspects of patient safety culture that could be improved. The dimensions of working conditions, work pressure and pace, and non-punitive response to error were the most frequently observed. Conclusion: The dimensions of management perception, working conditions, job satisfaction, work pressure, and speed, leadership support, staff training, incident reporting frequency, staffing, non-blame response, and hands-off and transition have low scores and require improvement in measuring patient safety culture.